Evaluation of melatonin efficacy in prevention of bronchopulmonary dysplasia in preterm newborn infants - Gharehbaghi, Manizheh Mostafa; Yeganedoust, Sadollah; Shaseb, Elnaz; Fekri, Majid (The Turkish Journal of Pediatrics, 2022)
Background. Excessive production of reactive oxygen species play an important role in the pathogenesis of bronchopulmonary dysplasia (BPD). Melatonin is an effective antioxidant and free radical scavenger. The aim of this study was to evaluate the efficacy of melatonin in the prevention of BPD in preterm infants with respiratory distress syndrome. Methods. In a randomized clinical trial, 80 preterm newborn infants with respiratory distress syndrome and gestation age of 27-32 weeks were allocated randomly in two groups. Group A consisted of 40 neonates who received surfactant with the INSURE technique. Patients in group B received melatonin 5mg/kg /day per gastric tube for 3 days in addition to the surfactant. The primary outcome was on the occurrence of BPD. The secondary outcome was considered other complications of prematurity, duration of hospital stay and mortality. Results. The mean gestational age and birth weight of studied patients were 31.3±3.8 weeks and 1189±84 grams, respectively. Thirty-five (43.8%) patients were girls and 45 (56.2%) were boys. BPD was diagnosed in 24 (60%) neonates of group A and 18 (45%) patients in group B, p=0.02. The duration of hospital stay, need for mechanical ventilation and mortality rate were significantly lower in patients in group B (p=0.02, 0.003, 0.009 respectively). Conclusions. Our study results showed that BPD, mortality and hospital stay reduced with melatonin treatment in preterm infants. However, future studies with a larger number of patients are needed to confirm these beneficial effects.
Keywords: bronchopulmonary dysplasia; melatonin; preterm infants; respiratory distress syndrome